(untitled) (Politeja, 2017)
Between independence and European Union. Paradoxes of the Scottish National Party’s attitude towards Brexit The purpose of this article is to explain the attitude of the Scottish National Party (SNP) towards European integration, based on a study of its activity in two campaigns – before the independence referendum in Scotland in 2014 and the referendum on continued membership of the United Kingdom in the European Union (EU) in 2016. Reciprocal links between the two events are perceptible even to a passing observer of the British Isle’s political life. The question of the EU membership was one of the most important topics in the independence referendum’s campaign, and the result of the European referendum has been widely interpreted in the context of the second independence referendum. By analyzing and comparing the referendum’s campaigns in the 2014 and 2016 and the period immediately after the announcement of the results of a European referendum, it can be seen that SNP presented the pro‑European stance in each of them, but using different sets of arguments. The concept of paradox, used in paper’s title, is a summary of a number of observations regarding the SNP’s complex relationship with the project of European integration. Although the aim of the party is to regain independence, the limitations of sovereignty, which according to many are associated with membership in the EU, do not raise critical assessment. The support for the European integration continues unabated despite the dominance of negative attitudes towards the Scottish independence movement among the European elites. Similarly, the party seems not to notice the level of euroscepticism among its electorate. And finally, what is the most interesting – on the one hand, the possibility of another independence referendum has not resulted in a change of the attitude towards Brexit, on the other hand in the same campaign it could be seen, that for SNP maintaining public support and a dominant position in relations with other parties in Scotland was more important that preventing Brexit.